2019
DOI: 10.1177/0886260519829763
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Rape Acknowledgment and Mental Health Outcomes Across Transgender, Nonbinary, and Cisgender Bisexual Youth

Abstract: The purpose of this study was to document the rates of rape acknowledgment (labeling rape as rape rather than using a minimizing label) and the corresponding mental health correlates using the minority stress framework in a unique and vulnerable sample: racially diverse sexual and gender minority young adults. Participants were 245 young adults who identified their sexual orientation as under the bisexual umbrella. A total of 159 of these participants (65.2%) identified their gender identity as nonbinary. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…As reported elsewhere (Anderson, Tarasoff, VanKim, & Flanders, 2019), rates of sexual violence reports were very high amongst participants. A total of 198 participants (80.8%) reported prior completed verbal coercion, and 202 participants (82.4%) reported prior completed rape.…”
Section: Descriptive Resultssupporting
confidence: 71%
“…As reported elsewhere (Anderson, Tarasoff, VanKim, & Flanders, 2019), rates of sexual violence reports were very high amongst participants. A total of 198 participants (80.8%) reported prior completed verbal coercion, and 202 participants (82.4%) reported prior completed rape.…”
Section: Descriptive Resultssupporting
confidence: 71%
“…Littleton et al () found many of the same predictors of acknowledgment in a sample of predominantly Latina or African American low‐income women as found in prior samples of predominantly white college women, though racial/ethnic comparisons were not made. Researchers have also found college men are less likely to acknowledge rape than women (Boyle and Walker ), and persons of color are more likely to acknowledge rape than white participants (Anderson et al ). While important, such research does not address how social identities shape victimization identities, still tending to focus on definitions of “rape” rather than self‐conceptualizations.…”
Section: “Victims” and “Survivors” Of Sexual Violencementioning
confidence: 99%
“…The rate of sexual violence victimization endured by the small population of gender minority participants in this study was 100%, in line with literature suggesting the risk of sexual violence for gender minorities is very high (Stotzer, 2009); we strongly recommend future research with this community and other diverse populations. It may be that sexual and gender minorities would benefit from measures designed with their specific needs and risks in mind (Anderson, Tarasoff, VanKim, & Flanders, 2019). Finally, the efficacy of efforts to reduce the risk of sexual violence may be inaccurately assessed, especially in under-studied and disadvantaged populations, if the assessment of prevalence rates are inaccurate.…”
Section: Implications For Clinical Work Prevention and Policymentioning
confidence: 99%